LUDWIG WITTGENSTEIN'S CONCEPT OF THE FORM OF LIFE (Eureka Journal of Humanities and Social Research, 2026)
This article examines the concept of “forms of life” in the philosophy of Ludwig Wittgenstein, focusing on its theoretical significance within his later works, particularly Philosophical Investigations. The study analyzes the role of forms of life as the foundational background that makes language, meaning, and understanding possible. It argues that Wittgenstein’s notion of forms of life reflects a shift from abstract and formal accounts of meaning toward a socially embedded and practice-oriented perspective.The research explores how forms of life function as a framework for language-games, shaping the rules, norms, and contexts in which linguistic expressions acquire meaning. Special attention is given to the interdependence between language and human activities, demonstrating that meaning is inseparable from the shared practices and cultural patterns of a community. The article also highlights the anti-essentialist and anti-metaphysical character of this concept, emphasizing its role in overcoming traditional dualisms such as subject–object and individual–society.
Keywords: Forms of life, language-games, meaning, social practices, rule-following, Wittgenstein, philosophy of language, normativity, communication, cultural context.